HYALURONIC ACID PRODUCTION AND ANALYSIS FROM ROOSTER COMB - (:unkn) unknown (IEEE, 2020)
Hyaluronic acid (HA) is a linear natural polymer, polysaccharide, with a high water affinity, biocompatible, called glucosaminoglycan. It is the preferred material in bioengineering research with its biodegradability, biodegradability and biofunctionality. In this study, hyaluronic acid was produced by chemical extraction from the rooster needle, which has not been evaluated much in our country. In addition, Fourier Transform Infrared Spectroscopy and Proton Nuclear Magnetic Resonance Spectroscopy analysis of the produced hyaluronic acid was performed. As a result, it has been shown that hyaluronic acid, a product with high added value, can be produced from cock crests by chemical methods.
Keywords: Hyaluronic acid (HA); production method; rooster, comb; extraction; STREPTOCOCCUS-ZOOEPIDEMICUS